Introduction to Higher-Order Iterative Methods for Finding Multiple Roots of Nonlinear Equations - Rajinder Thukral (Journal of Mathematics)
We introduce two higher-order iterative methods for finding multiple zeros of nonlinear equations. Per iteration the new methods require three evaluations of function and one of its first derivatives. It is proved that the two methods have a convergence of order five or six.